HR Retention Strategies for Enhanced Job Satisfaction in a Highly Competitive Job Market: A Study with Private Banking Sector in Bangladesh - Ahad, Abdullah Al; Khan, Md. Rahat; Rahman, Md. Safiar (International Journal of Social Sciences Perspectives, 2020)
Many studies have been conducted to find out the employee retention strategies by the organization towards issues related with HR. In this particular research the researchers tried to research and observe the relationship between employee retention and job satisfaction in private banking sector in the context of Bangladesh. A number of 150 sample size was considered through convenient sampling technique to analyze the relationship between satisfactions of employee on job retention strategies. The result of the correlation analysis found employee retention strategies is positively and strongly correlated with employee job satisfaction (r = 0.533, p < 1.00). In this regression analysis, the study found R2 = .284 which means independent (employee retention) variable can explain 28.4% of dependent variable (employee satisfaction) and the Independent variable employee retention can explain is positively depending on dependent variable employee satisfaction.